Sustainable Leather Garment Research and Design based on Geometric Tessellation Theory - Yingtong LIU; Chenyu ZHANG; Wei WANG (Pige Kexue Yu Gongcheng)
The green development of fashion industry requires a sustainable design concept with humanistic care. A method for sustainable leather clothing design was proposed based on geometric inlay. Leather garments were deconstructed into assembleable inlay modules, creating a diverse range of styles through assembly and providing consumers with the joy of participation in production and highly personalized features. Moreover, different inlay modules could be assembled according to demand to alter the garment's silhouette. Sustainable biomaterials and laser cutting technology were utilized in the production of inlay modules, aligning with the principles of sustainable design in terms of materials and production techniques. Practical results demonstrate that sustainable leather clothing based on geometric inlay enriches the form of garment products and provides innovative references for the development of leather products, clothing, and fashion design.